An oral combined contraceptive user with elevated D-dimer post COVID-19: a case report - Nada A. Alyousefi (BMC, 2021)
Abstract Background This case discusses the challenges created by COVID-19 (coronavirus disease 2019) in the area of hormonal contraception, highlighting the contraception knowledge gap for women in their post COVID-19 period, especially if they had high D-dimer levels. Case presentation This case involves a thirty-eight-year-old woman taking combined oral contraception (desogestrel/ethinyl oestradiol tablets) with a history of varicose veins. She recovered from a COVID-19 infection in November 2020. She presented to the emergency room with right lower-limb pain below the knee and progressive swelling for five days in February 2021. Physical examination of the lower limb showed mild swelling and tenderness of the right leg compared to the left leg. D-Dimer was elevated (1.06 mcg/mL FEU). COVID-19 screening was negative. A Doppler scan to exclude DVT was performed considering the clinical picture and high D-dimer level. There was no evidence of DVT in the right limb. She was reassured and discharged with instructions on when to visit the emergency room. The D-dimer had decreased to 0.53 mcg/mL FEU in March 2021. She booked an appointment with family medicine clinics because she was concerned about the continuation of combined oral contraception (desogestrel/ethinyl oestradiol tablets) with high D-dimer and risk of thrombosis. The follow-up D-dimer level in May 2021 was normal (0.4 mcg/mL FEU). The patient preferred to continue taking oral contraception. Conclusion An evidence-based consensus is needed to guide clinicians in providing contraception counselling for such patients.